Interpretacion de los resultados de las pruebas de pantalla y multipanel de celulas, en muestras de sangre de mujeres multiparas que requieran de transfusiones hematicas, atendidas por el servicio de medicina transfusional del hospital general docente de riobamba, durante el periodo mayo – octubre del 2013. - Ocaña Guaman, Maria Belen (2014)
This research work basic knowledge about the interpretation of the test results screen and multi panel of cells in blood samples from multiparous women requiring hematological transfusions, who are helped by the tranfusion medicine service of the General Teaching Hospital Riobamba.